2014
DOI: 10.1155/2014/407065
|View full text |Cite
|
Sign up to set email alerts
|

IVIVC from Long Acting Olanzapine Microspheres

Abstract: In this study, four PLGA microsphere formulations of Olanzapine were characterized on the basis of their in vitro behavior at 37°C, using a dialysis based method, with the goal of obtaining an IVIVC. In vivo profiles were determined by deconvolution (Nelson-Wagner method) and using fractional AUC. The in vitro and in vivo release profiles exhibited the same rank order of drug release. Further, in vivo profiles obtained with both approaches were nearly superimposable, suggesting that fractional AUC could be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Due to the expense, time, labor, and need for human subjects/animals when performing in vitro measurements of drug release kinetics, in vitro release is gaining greater attention as a surrogate test for product performance. Indeed, in vitro release testing is commonly used as a predictor of in vivo behavior, historically with traditional dosage forms like capsules and tablets (i.e., dissolution), and more recently with novel dosage forms like injectable biodegradable microspheres and implants [15][16][17]. Generally, in vitro release studies are performed at 37 ∘ C (physiological temperature), though in some instances testing at elevated temperatures has been explored to characterize drug release from a variety of dosage forms [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the expense, time, labor, and need for human subjects/animals when performing in vitro measurements of drug release kinetics, in vitro release is gaining greater attention as a surrogate test for product performance. Indeed, in vitro release testing is commonly used as a predictor of in vivo behavior, historically with traditional dosage forms like capsules and tablets (i.e., dissolution), and more recently with novel dosage forms like injectable biodegradable microspheres and implants [15][16][17]. Generally, in vitro release studies are performed at 37 ∘ C (physiological temperature), though in some instances testing at elevated temperatures has been explored to characterize drug release from a variety of dosage forms [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the polymer type and the incorporated therapeutic agent, the polymeric dosage form can provide sustained drug levels for varying durations in vivo [10,11]. Indeed, research has shown that these therapeutic agents have varying physicochemical properties that could alter polymer degradation and thereby alter drug release profiles [12][13][14][15][16]. This highlights the need to investigate the effect of a drug on polymer degradation as it can be critical with respect to product performance, as cited by several authors [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Another property of the PLGA polymer that has been used to customize drug release is its molecular weight [29][30][31]. Intuitively, it has been established that the larger molecular weight PLGAs degrade slower than the lower molecular weight polymer.…”
Section: Introductionmentioning
confidence: 99%